MicroRNA Profiling of Sendai Virus-Infected A549 Cells Identifies miR-203 as an Interferon-Inducible Regulator of IFIT1/ISG56 - Buggele, William A. (American Society for Microbiology, 2013)
The mammalian type I interferon (IFN) response is a primary barrier for virus infection and is essential for complete innate and adaptive immunity. Both IFN production and IFN-mediated antiviral signaling are the result of differential cellular gene expression, a process that is tightly controlled at transcriptional and translational levels. To determine the potential for microRNA (miRNA)-mediated regulation of the antiviral response, small-RNA profiling was used to analyze the miRNA content of human A549 cells at steady state and following infection with the Cantell strain of Sendai virus, a potent inducer of IFN and cellular antiviral responses. While the miRNA content of the cells was largely unaltered by infection, specific changes in miRNA abundance were identified during Sendai virus infection. One miRNA, miR-203, was found to accumulate in infected cells and in response to IFN treatment. Results indicate that miR-203 is an IFN-inducible miRNA that can negatively regulate a number of cellular mRNAs, including an IFN-stimulated gene target, IFIT1/ISG56, by destabilizing its mRNA transcript.